Korzhenevski Vladislav Vyacheslavovich (on the occasion of the 60-th anniversary of his birth) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Korzhenevski Vladislav Vyacheslavovich (on the occasion of the 60-th anniversary of his birth)